Kajian Eksekusi Jaminan Fidusia dalam Pelunasan Utang Piutang: Studi Komparatif Eksekusi dalam Hak Tanggungan dan Fidusia - Resty Iranda (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research discusses the study of execution in debt settlement with a comparison of several executions. The research method used is normative juridical with a legislative approach and a conceptual approach. The research results show that execution in fiduciary law can be carried out in three ways, namely the implementation of an executorial title, sale thru public auction (parate executie) and private sale, while still considering the Constitutional Court Decision Number 18/PUU-XVII/2019. In mortgage law, execution can be carried out thru parate execution, an executorial title and private sale, which have more definite legal force. Execution thru debt collectors cannot be justified because it lacks a valid legal basis.